ROA Performance Evaluation: Is Islamic Banking More Resilient to Crises Than Conventional Banking? - Tarishah Putri Arini; Tubagus Thresna Irijanto; Noraziah Che Arshad (AL-FALAH : Journal of Islamic Economics, 2026)
Purpose: This study aims to analyze and compare profitability resilience between Islamic and mainstream banking institutions in Indonesia during the COVID-19 pandemic. It tests the hypothesis regarding the resilience of the Islamic banking system based on profit-and-loss-sharing principles. Design/Method/Approach: Using Return on Assets (ROA) as the primary indicator, the research analyzes quarterly data from the three largest banks in each group (conventional: Bank Mandiri, BRI, BCA; Islamic: BSI, CIMB Niaga Syariah, BTN Syariah) for the 2018–2024 period. Correlation analysis is employed to assess the relationship between the two systems' performance. Findings: While conventional banks consistently had a significantly higher average ROA, Islamic banks demonstrated better relative resilience post- crisis. This is reflected in a greater increase in ROA (+0.222 points vs +0.066 points) and a reduction in performance volatility. Further correlation analysis revealed a decoupling phenomenon or separation in the movement of ROA between the two systems, indicating distinct recovery paths and risk characteristics. Originality/Values: The findings highlight conventional banks' advantage in absolute profitability while confirming the structural resilience of Islamic banking in the face of external shocks. The identification of a decoupling phenomenon in ROA movements offers new insight into the distinct recovery dynamics and risk profiles of Islamic versus conventional banking systems during a major crisis.